Legal Implications of the Authority of Acting Regional Heads Based on Policy Regulations - Hananto Widodo; Dicky Eko Prasetio; Ridwan Arma Subagyo; Sunanta Chemaming (Universitas Negeri Surabaya, 2024)
The expansion of the authority of acting regional heads following the enactment of Circular Letter (SE) Number 821/5492/SJ actually raises legal issues. The legal issues include the legal certainty of the Circular Letter, which is a policy regulation and not externally binding, and is in conflict with statutory regulations. This research focuses on the legal implications of the authority of acting regional heads to dismiss and transfer ASN based on legal products in the form of SE, where the authority of acting regional heads is based on Law No. 10 of 2016. This research is a normative legal study that emphasizes a conceptual and legislative approach. Research findings indicate that the existence of Circular Letter (SE) Number 821/5492/SJ, which expands the authority of acting regional heads, has implications that create legal uncertainty. The recommendation from this research is that amendments to Law Number 23 of 2014 are necessary to clearly regulate the authority of acting regional heads.